Research trends in meaningful learning in distance education environments: A review of articles published in Q1 to Q3 indexed journal from 2012 to 2022 - Nita Lestari; Murni Winarsih; Dwi Kusumawardani (Jurnal Inovasi Teknologi Pendidikan, 2023)
This study aims to investigate the idea that there is a functional and efficient mechanism for meaningful learning. This study is a literature review with various references to data sources. This study's essential focus is on the difficulties and possibilities of meaningful distant learning. An amount of 21 publications had released between 2012 and 2022. Use the SEforRA.com search engine to find information for research. Thematic Analysis to examine the results and show the findings. The research findings shed light on several topics related to meaningful learning, including perceptions, challenges for teachers and students on distance meaningful education, and learning practices. The findings also explain how meaningful learning is in distance learning. The Results show that meaningful learning activities incorporated into distance learning activities enable teachers and students will gain authentic and meaningful experiences that will benefit their education, such as adding teachers' insights for their future teaching practices. The outcomes of this exploratory study have several consequences for anyone involved in remote education, including administrators, teachers, instructional designers, and policymakers, who want to ensure that students have meaningful educational experiences.